The Role of Teachers in Educating Students' Religious Attitudes in Senior High School - Safira, Bela; Anita Indria (STIT Ahlussunnah Bukittinggi, 2024)
Islamic Religious Education has a strategic role in shaping the character and religious personality of students, especially in formal educational environments such as madrasahs. In an increasingly complex social context, strengthening religious values ​​is very important to protect the younger generation from negative influences that are contrary to Islamic teachings. Therefore, schools as educational institutions have a responsibility to implement Islamic Religious Education values ​​systematically in the learning process and student development. This study aims to determine how the implementation of Islamic Religious Education values ​​​​in developing students' religious attitudes at Madrasah Aliyah Nurul Iman Modong, South Sumatra. This type of research is field research with a qualitative descriptive approach. Data sources in this study include the Principal, Teachers, and grade XI students at MA Nurul Iman Modong. Data collection techniques used are observation, interviews, and documentation. The results of the study show that: (1) The values ​​​​of Islamic Religious Education implemented in learning include moral, spiritual, worship, and social Islamic values, which significantly contribute to the formation of students' religious attitudes; (2) Islamic Religious Education plays an active role in shaping students' religious awareness, both through intracurricular and extracurricular activities, such as congregational prayer, Al-Quran recitation, and moral development through teacher role models. The implications of this study indicate that internalization of Islamic Religious Education values ​​must continue to be improved through an integrative approach between teaching, habituation, and ongoing development. This is important to create a generation that is not only intellectually intelligent, but also spiritually strong and has noble morals.